2021
DOI: 10.1038/s41420-020-00387-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-541-3p enhances the radiosensitivity of prostate cancer cells by inhibiting HSP27 expression and downregulating β-catenin

Abstract: Heat shock protein 27 (HSP27), a regulator of cell survival, can enhance the resistance of cancer cells to radiotherapy. As microRNA-541-3p (miR-541-3p) was recently predicted to be a putative upstream modulator of HSP27, the present study was designed to investigate the function and mechanism underlying how miR-541-3p modulates the radiosensitivity of prostate cancer (PCa) cells by regulating HSP27. Through quantitative PCR, miR-541-3p was determined to be poorly expressed in PCa tissues relative to normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…More recently, miRNA-541-3p was studied in 33 PCa tissues and normal adjacent tissues before and after RT treatments. Interestingly, He et al found that miRNA-541-3p enhances the radiosensitivity of PCa by inhibiting HSP27 expression and downregulating β-catenin ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, miRNA-541-3p was studied in 33 PCa tissues and normal adjacent tissues before and after RT treatments. Interestingly, He et al found that miRNA-541-3p enhances the radiosensitivity of PCa by inhibiting HSP27 expression and downregulating β-catenin ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…MiR-541-3p has low expression in PCa tissues, however, when submitted to RT is overexpressed in PCa cells (LNCaP, DU-145, PC3, and PrEC). Thus, using the mimic approach, miRNA-541-3p interacted directly with HSP27 and increased the radiosensitivity by enhanced apoptosis ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…The potential relevance of Wnt/β-catenin signaling in mediating RT/CRT resistance has been demonstrated in other tumor entities, including CRC [ 23 , 24 , 48 , 49 ], prostate cancer [ 50 ], lung cancer [ 51 ], head and neck cancer [ 52 ], breast cancer and mammary gland cells [ 53 ], nasopharyngeal cancer [ 54 ], glioblastoma [ 55 ], and pancreatic cancer [ 56 ]. Although these reports underpin the relevance of Wnt/β-catenin signaling for radioresistance, the underlying mechanisms are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…There were three male specific differentially expressed miRNAs across gestation from the miR-376 precursor, miR-376a-3p, miR-376a-5p, and miR-376b-3p, all upregulated in third trimester. All of these miRNAs have been associated with cancer including reproductive cancers [76-79], which may be suggestive that these miRNAs are under sex hormone control, which is fetal sex specific early in gestation during fetal sex differentiation [80, 81]. The sex specific differences across gestation in C14MC and C19MC may account for differences in the identified canonical pathways.…”
Section: Discussionmentioning
confidence: 99%